Effectiveness of Training on Work Motivation - Armin Anwar (Cendekiawan Indonesia Timur, 2021)
This research aims to identify and evaluate the impact of training efficacy on the job motivation of local government workers. This research employs a literature review and a qualitative method. Purposive sampling is used to identify informants, and researchers choose informants. Techniques for gathering data include observation, interviews, and documentation. Data reduction, visualization, and conclusion drafting are all part of the data analysis process. The findings revealed that training efficacy directly impacts employee work motivation; successful training promotes changes in organizational systems for careers and skills to employee work motivation. The same idea has inspired workers effectively in professional advancement via career planning.